SAT0460 Association of the Hypoxia-Inducible Factor 1A (Hif1Alpha) Gene Polymorphism in Japanese Systemic Sclerosis (SSC) with the Pulmonary Arterial Hypertension (PAH). (9th June 2015) - Takagi, K.; Kawaguchi, Y.; Kawamoto, M.; Higuchi, T.; Tochimoto, A.; Ichida, H.; Ichimura, Y.; Ota, Y.; Yamanaka, H.
Abstract : Background: SSc is characterized by tissue fibrosis and peripheral circulatory insufficiency. Survival of SSc is influenced by the involvement of PAH. HIF1α is guided in a hypoxic condition and works as a transcription factor. HIF1α stimulates the transcription activity of the vascular endothelial growth factor (VEGF), while the ligand of the VEGF receptor family exhibits cell proliferation and angiogenesis. Association of HIF1α with various ischemic diseases, such as ischemic heart disease, type II diabetes or neoangiogenic condition like cancer has been reported. Based on these observations, one can hypothesize that HIF1α may be involved in tissue fibrosis in SSc indirectly through VEGF. However, it has not been clarified how HIF1α is associated with the pathogenesis of SSc. Intriguingly, Wipff et al. reported that single nucleotide polymorphism (SNP) of HIF1A gene, rs12434438, was associated with the development of SSc in Caucasian of France. Objectives: The purpose of the present study is to evaluate whether the SNPs of the HIF1A gene are associated with susceptibility to SSc and the development and complications in SSc. Methods: A retrospective case control study involving 182 Japanese SSc patients and 178 healthy matched controls were performed. The patients who had ischemic heart disease, type II diabetes and cancer were excluded. Four types of SNPs (rs11549465, rs11549467, rs1957757, and rs12434438) of the HIF1A gene were genotyped using the Taqman probes. The frequencies of these genotypes and the association of clinical symptoms, disease type, complications, and SSc specific antibodies were analyzed. Significance tests for deviation from Hardy-Weinberg equilibrium of these SNPs were performed using Pearson χ 2 -test. GRR (genotype relative risk) and HRR (Haplotype relative risk) between the cases and controls were investigated using fisher's exact test and odds ratio (ORs). Results: The frequencies of these 4 SNPs did not show the significant differences between control healthy people and SSc patients in Japanese population. However, the frequency of rs12434438 AA genotype was significantly higher in PAH developed SSc patients (p<0.05). Moreover the frequency was much higher in the group receiving home oxygen therapy and the group of New York Heart Association (NYHA) class III and IV status (p<0.05). Hap Map-JPT and Hap Map-CEU describes AA frequencies of rs12434438 is lower in Japanese population compared to that of European. These observations suggest contribution of rs12434438 to SSc development and PAH development in SSc, may be different among races. Moreover, rs1234438 genotype AA can be used as a prognostic predictor for sever PAH development, rather than risk of SSc development in Japanese population. Conclusions: Four types of SNPs (rs11549465, rs11549467, rs1957757, and rs12434438) in the HIF1A gene were not associated with disease susceptibility in Japanese SSc patients. The frequency of rs12434438 AA genotype was higher in sever PAH group in SSc. The rs12434438 would contribute to the onset and severity of PAH in Japanese SSc patient. References: Wipff J, et, Association of hypoxia-inducible factor 1A (HIF1A) gene polymorphisms with systemic sclerosis in a French European Caucasian population. Scand J Rheumatol. 2009; 38(4):291-4 Disclosure of Interest: None declared